Implementation of Big Data Migration on PIS-PK System Database to Mhealth System Database Using ETL and Queue (Ministry of Health Case Study) - Haqqu, Raindeca Dzulikrom; Hustinawati , Hustinawati (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research explores the implementation of big data migration from the PIS-PK (Pusat Informasi Sistem - Pangkalan Data Kesehatan) system database to the Mhealth system database using ETL (Extract, Transform, Load) processes and queue management. The case study focuses on the Ministry of Health, where large-scale health data needs to be transferred between systems to improve efficiency, accessibility, and integration with modern health technologies. The research investigates the challenges involved in migrating extensive data sets, such as maintaining data integrity, handling different data formats, and ensuring smooth data flow during the migration process. By implementing ETL techniques, the study ensures that data is extracted, transformed, and loaded into the Mhealth database while maintaining consistency, quality, and structure. Furthermore, the use of queue systems is explored as a mechanism to handle data processing asynchronously, enabling the smooth transfer of large volumes of data in real-time. The study concludes with a set of best practices for managing big data migration in healthcare systems and highlights the potential benefits of enhancing the Ministry of Health’s database architecture for future health data management and analytics. This migration is expected to streamline healthcare data processes, improve decision-making, and support the Ministry's digital health initiatives.